2012
DOI: 10.1371/journal.pone.0041619
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Simvastatin or Interferon-α on Infectivity of Human Norovirus Using a Gnotobiotic Pig Model for the Study of Antivirals

Abstract: The lack of an animal model for human norovirus (HuNoV) has hindered the development of therapeutic strategies. This study demonstrated that a commonly used cholesterol-lowering statin medication, simvastatin, which increases HuNoV replication in an in vitro replicon system, also enhances HuNoV infectivity in the gnotobiotic (Gn) pig model. In contrast, oral treatment with interferon (IFN)-α reduces HuNoV infectivity. Young piglets, all with A or H1 histo-blood group antigens on enterocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 53 publications
6
98
0
Order By: Relevance
“…Swine have HBGA phenotypes similar to those of humans, making gnotobiotic piglets an excellent model with which to study human NoVs (23-25, 35, 36). Previous studies have shown that gnotobiotic piglets are susceptible to oral infection with several human NoV GII.4 strains, and this animal model has been used for evaluation of the efficacy of vaccine candidates and antiviral therapies against human NoVs (23)(24)(25)37). We found that gnotobiotic piglets inoculated with human NoV GII.4 strain 765 exhibited mild diarrhea, viral RNA shedding in feces, histologic lesions in the intestines, and viral replication in the proximal small intestine.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Swine have HBGA phenotypes similar to those of humans, making gnotobiotic piglets an excellent model with which to study human NoVs (23-25, 35, 36). Previous studies have shown that gnotobiotic piglets are susceptible to oral infection with several human NoV GII.4 strains, and this animal model has been used for evaluation of the efficacy of vaccine candidates and antiviral therapies against human NoVs (23)(24)(25)37). We found that gnotobiotic piglets inoculated with human NoV GII.4 strain 765 exhibited mild diarrhea, viral RNA shedding in feces, histologic lesions in the intestines, and viral replication in the proximal small intestine.…”
Section: Discussionmentioning
confidence: 73%
“…Second, we determined the infectivity of human NoV following HPP treatment in a gnotobiotic pig model. The gnotobiotic pig is an excellent model for human enteric viruses because pigs share many similarities with humans in gastrointestinal structure, physiology, immunology, and, more importantly, the HBGA phenotypes (types A and H) on enterocytes (23)(24)(25)(26)(27). We found that HPP treatment at 350 MPa for 2 min at an initial temperature of 0°C reduced the amount of human NoV in oysters by approximately 3.7 log 10 units, as determined by a combination of a receptor binding assay and real-time reverse transcription-PCR (RT-PCR).…”
mentioning
confidence: 99%
“…The study of human noroviruses (HuNV) has been impeded by the absence of a viable cell culture system for this pathogen and the fact that baby gnotobiotic pigs are the only available smallanimal model (4,5). As a result, other caliciviruses have often been used as surrogate models for the investigation of HuNV biology (6).…”
mentioning
confidence: 99%
“…The recombinant baculovirus (rBac) carrying the VP1 gene (ORF2) of the Hu/NoV/GII.4/HS194/2009/US strain (GenBank accession number GU325839) was produced using the BaculoDirect baculovirus expression system (Invitrogen, Carlsbad, CA). The Gateway entry clone containing the capsid protein (VP1) of HS194 (pENTR/SD/D-TOPO-HS194) was generated and used with BaculoDirect linear DNA to perform an LR (attL [entry clone] ϫ attR [destination vector]) recombination reaction to generate recombinant baculovirus DNA carrying the VP1 gene of HS194 (25). Sf9 cells were cultured at a density of 3 ϫ 10 7 cells/flask (162 cm 2 ) and inoculated with rBac GII.4 at a multiplicity of infection (MOI) of 10, after which the medium was harvested at 10 days postinoculation.…”
Section: Methodsmentioning
confidence: 99%